2021
DOI: 10.1016/j.cmi.2020.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Dalbavancin exposure in vitro selects for dalbavancin-non-susceptible and vancomycin-intermediate strains of methicillin-resistant Staphylococcus aureus

Abstract: Objectives: Dalbavancin is a lipoglycopeptide active against methicillin-resistant Staphylococcus aureus (MRSA). Its long half-life (8.5e16 days) allows for once-weekly or single-dose treatments but could prolong the mutant selection window, promoting resistance and cross-resistance to related antimicrobials such as vancomycin. The objective of this study was to evaluate the capacity of post-distributional pharmacokinetic exposures of dalbavancin to select for resistance and cross-resistance in MRSA. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
(33 reference statements)
1
33
0
Order By: Relevance
“…We also observed that one nsSNP (H271D) within the Zn 2+ -binding site (residue 271) was detected in a VISA strain 12 .…”
Section: Transcriptional Changes In Van-i Mutantsupporting
confidence: 52%
See 3 more Smart Citations
“…We also observed that one nsSNP (H271D) within the Zn 2+ -binding site (residue 271) was detected in a VISA strain 12 .…”
Section: Transcriptional Changes In Van-i Mutantsupporting
confidence: 52%
“…In the present study, an overview of the protein structure mapping of several previously reported nsSNPs in VISA strains indicated that WalK nsSNPs frequently occurred in the PAS CYTO domain 5,12,[27][28][29]33 . However, we observed that nsSNP could occur in every WalK protein domain.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…As such, most studies on daptomycin resistance point to development of mutations in genes that control membrane lipid metabolism and/or lead to changes in surface charge, membrane fluidity, or both, such as mprF, cls, pgsA, and the dlt operon, which reduces binding of daptomycin to the cell membrane or prevents disruption of the membrane by daptomycin (Yang et al, 2009;Peleg et al, 2012;Mishra and Bayer, 2013;Bayer et al, 2014;Cafiso et al, 2014;Mishra et al, 2014;Bayer et al, 2015;Hines et al, 2017;Jiang et al, 2019). Mutations in two-component regulatory systems that regulate cell wall and cell membrane metabolism, such as vraSR and walKR (Friedman et al, 2006;Mehta et al, 2012;Werth et al, 2021), have also been shown to contribute to daptomycin resistance. We previously applied a novel multidimensional lipidomic method to characterizing the detailed lipid profile changes associated with MRSA strains that have developed resistance to daptomycin and found overall greatly decreased levels of PGs in a resistant strain with mutations in both pgsA and mprF (Hines et al, 2017) and greatly elevated levels of lysylphosphatidylglycerols (lysylPGs) and cardiolipins (CLs) in a strain with only an mprF mutation (Hines et al, 2020).…”
Section: Introductionmentioning
confidence: 99%